Effects of different amounts of organic fertilizers on growth and production of tilapia in monoculture (International Journal of Agricultural Research, Innovation and Technology, 2018)
The experiment was conducted to determine the effects of different amounts of organic fertilizers on growth and production of Tilapia (monosex GIFT tilapia) in monoculture system for a period of 120 days. The experiment was carried out in six earthen ponds, which were situated at the south-east corner of the Fisheries Faculty Building under the Department of Fisheries Management, Bangladesh Agricultural University, Mymensingh. The experiment was designed with three treatments and each of them consisted of two replications. Fish population density was 120 fish per decimal for all the treatments. Ponds were treated with organic fertilizers (cow dung) at the rate of 2 kg, 4 kg and 6 kg per decimal were supplied fortnightly for treatment-I, treatment-II and treatment-III, respectively. The ranges of water temperature, transparency, dissolved oxygen, total alkalinity, free CO2, phosphate-phosphorus and nitrate-nitrogen found were 15.82 to 24.49 ºC, 17.00 to 32.00 cm, 7.00 to 10.30 mg L-1, pH 7.20 to 7.90, 140.00 to 192.00 mg L-1, 2.00 to 6.00 mg L-1, 1.40 to 1.95 mg L-1 and 3.30 to 3.73 mg L-1, respectively. All the physical and chemical parameters except temperature were within the productive range and more or less similar among all the ponds under three treatments. 18 genera of phytoplankton under five major groups and 9 genera of zooplankton under three major groups were identified in the experimental ponds. Average survival rate of fish under treatment-I, treatment-II, and treatment-III were 94.50%, 94.00% and 95.00%, respectively. The calculated net fish production under treatment-I was 3.554 ton ha-1 yr-1 and that under treatment-II was 3.648 ton ha-1 yr-1 and under treatment-III was 2.919 ton ha-1 yr-1. The net fish productions under treatment-II and treatment-III were 102.64% and 82.13% comparing with treatment on which was taken for 100%. According to cost-benefit analysis, the ratios of net profit under treatments I, II, and III were 1:0.81, 1:0.54, and 1:0.04. According to specific growth rate, treatment-II was the best and survival rate of treatment-III was the best, and according to cost-benefit analysis, treatment-I (ratio 1:0.81) was the best. So, organic fertilizer at the rate of 2 kg per decimal (treatment-I) was considered the best among three treatments in this experiment.Int. J. Agril. Res. Innov. & Tech. 8 (2): 24-31, December, 2018